Environmental impact assessment for urban development (CEMP, 1997)
Participans introductions, presentation of the broad overview of key environmental impact assessment issues in urban development and management in Thailand. Introduction to key contemporary urban environmental management problems and issues and how EIA and planning and management tools can contribute to more sustainable forms of urban development,...